Child-Friendly Pesantren Concept: A Strategic Approach to Empowering Children's Rights - Nadlifuddin, Mohammad Ilham (The Institute of Research and Service Community IPMAFA Pati, 2024)
Pesantren has an important role in religious education and character-building for children. However, cases of uncovered violence in the Pesantren environment are still a concerning issue. This study aims to analyze the application of the Child-Friendly Pesantren concept as a model for protecting children from empowerment in the educational environment. This study uses a qualitative approach with a literature review method. Data sources include books, journal articles, research reports, and other relevant documents published between 2019 and 2023, which were accessed through Google Scholar. The results of the study show that although Pesantren contributes greatly to moral education, there are still challenges in ensuring a safe environment for children. The Child-Friendly Pesantren concept, which includes strict supervision, a safe complaint mechanism, children’s rights education, psychological support, and periodic evaluations, has proven to be a solution that can reduce the risk of violence and harassment in Pesantren. The application of the Child-Friendly Pesantren framework not only supports child protection but can also be used as a role model for other educational environments to create a safe, inclusive, and child-friendly atmosphere. The implementation of the Child-Friendly Pesantren concept can effectively increase child protection in Pesantren and make Pesantren a role model in child protection in educational environments.